Bent - Porter, G. (2009)
Colour Sandy Gow (director), Brian Bishop (lighting design), Shannon Hawes (sound design), Sam Pryse-Phillips (set design). Featuring Mack Furlong, Phil Goodridge, James Hawksley, Beni malone, Jon Montes, Keith Pike, Calvin Powell, George Robertso C2C Theatre